The Road to Seneca Falls: The Origins of the Woman's Rights Movement in the United States, 1800-1848 - Maybrey, Catherine (My University, 1998)
This thesis seeks to offer an explanation to the question of why Seneca Falls occurred. It attempts to examine those movements and societal conditions which prompted women to demand an improvement in female life. The thesis specifically explores the areas of female education, abolition, and legal reform. The material suggests that women in the nineteenth century underwent a gradual change in consciousness wherein they became more aware of their subordinate position in society and began to seek ways of changing it. While the study does not introduce any new historical figures, it does examine them in a new context. Sources have indicated that w10men such as Catharine Beecher and Lydia Maria Child, who held strongly conservative Views, managed to advance the cause of gender equality, regardless of their personal convictions. By examining the actions and consequences of leading female reformers in the nineteenth-century, I have demonstrated the gradual move towards feminism and woman suffrage.
Keywords: History; History